The role of maternal serum and breast milk adipokines in determining postpartum and infant adiposity development - Mohamad, Marhazlina (2016)
Obesity has been a great concern in Malaysia since there is an alarming increase in its prevalence. Besides storing fat, adipose tissue is also an endocrine organ that secretes a large number of adipokines. Pregnancy, a state with metabolic changes, has been recognized as a critical period for the development of maternal and infant adiposity as a result of imbalanced adipokines production. Hence, the Universiti Sains Malaysia Pregnancy Cohort Study was established to investigate the role of maternal serum and breast milk adipokines (adiponectin and leptin) in determining the first year postpartum weight retention (PPWR) and infant adiposity development. This study was conducted from April 2010 until December 2012. A total of 155 healthy pregnant mothers aged 19 to 40 years were recruited at first and second trimester of pregnancy in Kelantan, Malaysia. Data collection were consisted of maternal socio-demography, medical history, anthropometry, dietary, physical activity, physical discomforts and clinical biochemistry analysis; and infant’s anthropometry and feeding patterns. Fasting serum samples were taken during pregnancy for the serum glucose, lipid profile, adiponectin and leptin levels analyses. Breast milk samples were collected at birth and 2 months postpartum. Data collection was performed at second and third trimester of pregnancy, continued with follow-up visits at birth, 2 months, 6 months and 12 months postpartum. Multiple linear regression (MLR) analyses were performed to examine; 1) the associations of maternal serum adiponectin with breast milk adiponectin within 2 months postpartum; 2) the associations of prenatal factors and maternal serum adiponectin and leptin on 12 months PPWR; and 3) the associations of maternal serum and breast milk adiponectin and leptin on infant adiposity development. MLR models showed that breast milk adiponectin at birth increased with increasing maternal serum adiponectin atthird trimester (p=0.006), while breast milk adiponectin at 2 months postpartum increased with increasing maternal serum adiponectin at second and third trimesters respectively (p=0.035, p=0.006). At 12 months postpartum, PPWR increased with increasing weight gain rate (WGR) at third trimester (p<0.001), and decreased with increasing HDL-cholesterol at second trimester (p<0.001). In the first year of age, as maternal serum and breast milk adiponectin increased, infant weight, BMI-for-age Z-scores, abdominal circumference and triceps skinfold significantly decreased (p<0.05). In conclusion, 1) maternal serum adiponectin during pregnancy was associated with breast milk adiponectin within 2 months postpartum; 2) WGR and HDL-cholesterol during pregnancy were related with 12 months PPWR; and 3) maternal serum and/or breast milk adiponectin were associated with the first year infant adiposity development. The favourable results of breast milk adiponectin indicated the potential role of breastfeeding practice in the prevention of obesity since infanthood.